Quality Characteristics and Consumer Acceptance of High-Moisture Mozzarella Obtained from Heat-Treated Goat Milk - Michele Faccia; Giuseppe Gambacorta; Antonella Pasqualone; Carmine Summo; Francesco Caponio (Foods, 2021)
High-moisture mozzarella is a pasta filata cheese manufactured from cow or buffalo milk that has spread all over the world. Its manufacturing from the milk of small ruminants (goat and sheep) has been recently proposed to innovate this ailing sector. Previously, a protocol was reported for making goat mozzarella from unpasteurized milk but, according to legislation, the microbiological safety of raw milk fresh cheeses is not guaranteed. In the present research, two new protocols were tested for producing mozzarella from pasteurized milk prepared by two different low-temperature long-time treatments (67 °C or 63 °C × 30 min). The obtained cheeses were subjected to physical–chemical and microbiological analyses and to consumer testing. The results showed that the heat treatments caused longer coagulation times than those reported in the literature, despite pre-acidification (at pH 5.93 or 6.35) having been performed to counterbalance the expected worsening of the coagulation aptitude. The obtained products showed differences in the chemical composition, texture, proteolysis, and lipolysis. Both pasteurization and pre-acidification played a role in determining these variations. Consumer testing indicated that mozzarella obtained from milk heated at the lower temperature and coagulated at a higher pH reached a good level of appreciation (62%).